Oncogenic viruses as etiological risk factors for head and neck cancers: An overview on prevalence, mechanism of infection and clinical relevance. (November 2022) - Payaradka, Rajesha; Ramesh, Pushkal Sinduvadi; Vyas, Rahul; Patil, Prakash; Rajendra, Vinay Kumar; Kumar, Mohana; Shetty, Veena; Devegowda, Devanand
Abstract: Objective: This review article aims to discuss the role of oncogenic viruses in the development of head and neck cancers including the prevalence, mode of infection and the clinical relevance of these viral infections associated with tumours. Design: A detailed review of scientific literature was performed relevant to oncogenic viruses associated with head and neck cancers. Results: The incidence of head and neck cancers associated with traditional risk factors such as smoking, chewing tobacco and alcohol consumption have reduced gradually. With the emergence of oncogenic viruses, the viral infection has become a major etiological contributor to the global cancer burden. Viral infection in the etiology of cancer opens up an opportunity for viral gene specific targets in diagnosis and biomarkers to evaluate prognosis. Infection with high-risk HPVs in the oropharynx is already proving to be beneficial as a subset of HPV-positive oropharyngeal cancer patients tend to have better prognosis in terms of treatment responses and overall survival. Conclusions: Large multi-center clinical trials exploring the implications of modifying viral infections in cancers are further warranted and the results hold the key to the management of patients suffering from cancers driven by viral infections.